A Study of Scavenging Poultry Gastrointestinal and Ecto-parasites in Rural Areas of Matebeleland Province, Zimbabwe - Dube , S.; Zindi, P.; Mbanga, J.; Dube, C. (International Journal of Poultry Science, 2010)
A study was carried out to determine endo and ecto-parasites in Matebeleland North and South from free range chickens (Gallus domesticus). Only adult chickens were selected for determination of parasite. For intestinal parasites microscopic studies of eggs and faecal egg counts were done using the salt floatation technique. The endo parasites encountered in the study were Tetrameres americana, Acuaria hamulosa, Ascaridia galli, Heterakis gallinarum, H. dispar, Allodapa suctoria, Capillaria annulate, Raillietina echinobothrida and R. tetragona. A commercially prepared insecticide constituted as follows (0.02% Tetamethrin, 0.03% pramethrin and 0.034% Imiprothrin) was applied for 2 seconds and feathers were then gentle unruffled so that ectoparasites could be counted and identified. Ecto parasites recorded in this study were Menopon gallinae, Menacanthus stramineus, Dermanyssus gallinae, Argas persicus, Ornithonyssus bursa, Cnemidocoptes mutans, Echidnophaga gallinacean, Gonocoites gallinae and Gonocoites hologester. The birds under study showed slow growth, poor egg hatching. Parasites should have contributed substantially to this poor growth although not single handedly.